Isolek Bahasa Simalungun di Kecamatan Gunung Malela, Bandar, Bosar Maligas, Ujung Padang, Tanah Jawa, Kabupaten Simalungun - Nurjana Sihombing; Dwi Widayati (Peneliti.net, 2023)
This article aims to analyze the phonological and lexical variations of the Simalungun language in 5 sub-districts in Simalungun Regency. This research is a qualitative descriptive research. This research will be analyzed using the theory of structural dialectology. The data for this study came from speakers of Simalungun in 5 sub-districts in Simalungun Regency, which came from 200 Swadesh vocabularies. The data collection method used was the proficient method with fishing techniques as the basic technique and the all-round proficient technique as an advanced technique. The analytical method used is the matching method with the technique of sorting out the determinants as a basic technique and the comparative comparison technique equates and compares differentiates as an advanced technique. From this study it was concluded that the Simalungun language in the 5 sub-districts in Simalungun Regency has phonological variations, namely vocal variations [e] [i]/#V-. Vocal variations [Ø] [a]/#-. Vocal variations [i] [u]/#K-. Vocal variation [ɛ] [o]/#K-. Vocal variations [a] [i]/#K-. Vocal Variations [U] [ɔ]/-K#. Variation of diphthongs [ɛy] vocal [ɛ]/-#. Vocal variation [ɛ] diphthong [uy]/-#. Vocal variation [ɛ] diphthong [ɛy]/-#. Variation of vocals [o] diphthongs [ow]/-#. Consonant variations [Ø] [h]/#-. Consonant variations [s] [Ø]/#-. Consonant variations [Ø] [d]/#-. Consonant variations [n] [t]/#V- . Consonant variations [Ø] [m]/-V#. Consonant variations [h] [k]/#V-. Consonant variations [m] [b]/#V-. Consonant variations [r] [l]/#V-, as well as sound variations are symptoms of metathesis. There are 56 lexical variations of the Simalungun language from the 200 Swadesh vocabularies studied.